Commentary—Liberty’s Refuge, or the Refuge of Scoundrels?: The Limits of the Right of Assembly - Ashutosh Bhagwat (Washington University Law Review, 2012)
Liberty’s Refuge is an important book with a lot of original and interesting things to say about the First Amendment. In many ways, however, the best thing about this book is not just what it says, but how it says it. Impressively, while advancing strong and controversial positions, Professor Inazu somehow avoids the trap into which so much constitutional scholarship falls of purporting to provide a final and complete theory which provides the grounding for an entire area of law and rejecting all other perspectives as wrong-headed. Instead, this book self-consciously sets out to start a conversation about important questions: how and why forgotten First Amendment rights such as peaceable assembly should be revived, and what role assembly promises to play in the political process. This conversation promises to be a rich and exciting one.
Keywords: & quot; Liberty& #x27; s Refuge: The Forgotten Freedom of Assembly& quot; John Inazu; Freedom of assembly; Right to exclude; Group rights